2018
DOI: 10.1007/s10905-018-9665-1
|View full text |Cite
|
Sign up to set email alerts
|

Aversive Learning in the Praying Mantis (Tenodera aridifolia), a Sit and Wait Predator

Abstract: Animals learn to associate sensory cues with the palatability of food in order to avoid bitterness in food (a common sign of toxicity). Associations are important for active foraging predators to avoid unpalatable prey and to invest energy in searching for palatable prey only. However, it has been suggested that sit-and-wait predators might rely on the opportunity that palatable prey approach them by chance: the most efficient strategy could be to catch every available prey and then decide whether to ingest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…This scenario, from a more speculative perspective, suggests the possibility that the insect learned from the experience where and what to hunt. Mantids are known to use aversive learning to avoid toxic prey (Carle et al 2018), a first basic learning ability shared by many predators. This case, however, suggests a further step to a more articulated cognitive process, including the ability to learn not only from a single stimulus but from different environmental clues and experiences, for elaborate new hunting strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario, from a more speculative perspective, suggests the possibility that the insect learned from the experience where and what to hunt. Mantids are known to use aversive learning to avoid toxic prey (Carle et al 2018), a first basic learning ability shared by many predators. This case, however, suggests a further step to a more articulated cognitive process, including the ability to learn not only from a single stimulus but from different environmental clues and experiences, for elaborate new hunting strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we can rule out the possibility that some form of specific coevolutionary relationship between these two species may have influenced our results. Previous studies have found that mantids are capable of learning to avoid warningly coloured defended prey (Carle et al, 2018). Our finding that naïve mantids were wary of large caterpillars with eyespots at the outset, indicates that praying mantids have largely an innate rather than learned tendency to be cautious of large potential prey with eye-like stimuli.…”
Section: Discussionsupporting
confidence: 49%
“…While previous learning studies have used DB-treated prey [42,54,61] and diet-manipulated milkweed bugs [25,69] as aversive stimuli, here we scaled down these methods for use with smaller, understudied arthropod predators and thoroughly investigated the merits (and potential drawbacks) for each method. Our data therefore provide practical guidance for using these techniques effectively in future manipulative experiments that examine learning, foraging, and aposematism.…”
Section: Discussionmentioning
confidence: 99%
“…While quinine has long been used as a bittering agent in taste aversion studies with many animals [57][58][59], we chose to use DB here because quinine has been shown to be ineffective with at least some jumping spider species, which will readily eat quinine-laced prey [60]. In invertebrate predators, there are two main aversive conditioning studies (to our knowledge) that used DB, both of which manipulated the palatability of prey offered to mantids by injecting and coating prey with DB solution [61,62]. Despite its widespread effectiveness in studies with avian predators, and more recent use with mantid predators, little is known about the effectiveness of DB when applied solely to the surface of much smaller prey and offered to smaller invertebrate predators.…”
Section: Experimental Set 1: Db-induced Unpalatability In Termitesmentioning
confidence: 99%